Manolis Manoledakis (ed.). The Black Sea in the Light of New Archaeological Data and Theoretical Approaches. Proceedings of the 2nd International Workshop on the Black Sea in Antiquity held in Thessaloniki, 18–20 September 2015. - Donnellan, Lieve (Journal of Greek Archaeology, 2019)
That Black Sea studies have become a dynamic field over the last few years is demonstrated by this new volume, edited by Manolis Manoledakis. The book results from a workshop, organised in Thessaloniki in 2015. The title clearly states the book’s ambition: collect more data and shed a critical light on them. While the book successfully achieves the first ambition of collecting new data, the second aim – introducing new theoretical frameworks – has only been achieved to a moderate extent throughout the volume. Most of the contributions remain firmly within the established interpretative boundaries and contribute little to ongoing discussions of, for example, globalisation processes in the Ancient World, to name just one omission. Only a few papers adopt more challenging perspectives on (ethnic) identity or economic production.